Effect of passivation layers in bilayer with ZrO2 on Ge substrate for improved thermal stability - Won, Byoungjun; Oh, Geun Ha; Oh, Il Kwon (Journal of Materials Science, 2024)
In this study, the effects of Al2O3 and Y2O3 passivation layers on Ge substrates are investigated to enhance the thermal stability of Ge-based devices. Using X-ray photoelectron spectroscopy, we analyze the growth characteristics and chemical composition of Al2O3, Y2O3, and ZrO2 on Ge. The changes in the crystallinity of ZrO2 on different substrates of Ge, Al2O3/Ge, and Y2O3/Ge configurations are observed via X-ray diffraction. Material properties, including capacitance, flat band voltage shift (ΔVFB), oxide charge trap (Not), interface defect density (Dit), and leakage current, are analyzed using the metal–oxide–semiconductor capacitor, with a particular focus on their electrical characteristics. Additionally, we investigate whether the passivation mechanisms of each material are more suitable for enhancing thermal stability. Overall, this study provides insight into the role of passivation layers in improving the interface and thermal stability of Ge-based devices, offering valuable contributions to the advancement of semiconductor technology. Graphical abstract: (Figure presented.)
Keywords: Bi-layer; Chemical compositions; Cristallinity; Different substrates; Ge substrates; Growth characteristic; Passivation layer; Thermal; X-ray photoelectrons; ZrO 2